Internationalization of higher education institutions in the Philippines current trends and challenges - Sabio, Ralph A. (2012)
This paper focuses on the internationalization programs being undertaken by higher education institutions (HEIs) in the Philippines and its trends. To characterize internationalization efforts in the country, most HEIs consider various programs to entice foreign students. However, given the current efforts of HEIs, several issues have emerged in terms of internationalization trends such as relevance, the conservation of cultural characteristics amidst efforts to internationalize education, among others. This paper will limit its discussion to student mobility-specifically, the influx of foreign students in the Philippines during the recent years since the most common indicator of internationalization is the number of foreign students studying in the Philippines, this paper attempts to discuss the challenge that lie ahead among Philippine HEIs.
Keywords: Education (Higher)